2014
DOI: 10.1186/s12966-014-0124-x
|View full text |Cite
|
Sign up to set email alerts
|

Active transportation and public transportation use to achieve physical activity recommendations? A combined GPS, accelerometer, and mobility survey study

Abstract: BackgroundAccurate information is lacking on the extent of transportation as a source of physical activity, on the physical activity gains from public transportation use, and on the extent to which population shifts in the use of transportation modes could increase the percentage of people reaching official physical activity recommendations.MethodsIn 2012–2013, 234 participants of the RECORD GPS Study (French Paris region, median age = 58) wore a portable GPS receiver and an accelerometer for 7 consecutive day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 38 publications
7
95
0
2
Order By: Relevance
“…The consequences of various basic criteria of physical activity assessment, included in health-oriented recommendations, are quite significant differences in PA evalutaion even in the same study group (percentages of compliance with PA guidelines are unlike). A similar trend was observed in research conducted by Chastin et al (2009), Scheers et al (2013 and Chaix et al (2014) where the degree to which a PA recommendation was satisfied differed depending on the criterion used in the evaluation. There are still only few publications investigating this problem.…”
Section: Discussionsupporting
confidence: 82%
“…The consequences of various basic criteria of physical activity assessment, included in health-oriented recommendations, are quite significant differences in PA evalutaion even in the same study group (percentages of compliance with PA guidelines are unlike). A similar trend was observed in research conducted by Chastin et al (2009), Scheers et al (2013 and Chaix et al (2014) where the degree to which a PA recommendation was satisfied differed depending on the criterion used in the evaluation. There are still only few publications investigating this problem.…”
Section: Discussionsupporting
confidence: 82%
“…As previously described in detail, the RE-CORD participants were recruited during preventive health checkups in 2007-2008 and 2011-2013, born between 1928 and 1978, and resided at baseline in 112 municipalities of the I ˘ l e-de-France Paris region (5,7,13,34). In the second wave of the study (8,26), after undergoing a medical checkup and filling computerized questionnaires at the IPC Medical Centre (10,23), 410 individuals were invited to participate in the RECORD GPS study (9), of which 247 subjects agreed to participate. Nine participants abandoned the study, and data collection failed for two participants, thereby yielding a final participation and completion rate of 57.6% (n = 236).…”
Section: Methodsmentioning
confidence: 99%
“…This discrepancies in the observed results might be influenced mainly by the methodological approach (type of PAL assessment tool, mean age of the responders, ethnicity of the included subjects, their habits, etc.) [8,9,29,32].…”
Section: Resultsmentioning
confidence: 99%
“…Despite all the health benefits of PA, people worldwide do not practise it in suitable amounts [6]. An even greater problem is that children are less involved in any form of regular PA today [4,7], which might by influenced by environmental factors [8] and lifestyle [9,10]. Several previous studies suggested a benefit of regular PA on the health of young people and their potential to reduce the incidence of chronic diseases in adulthood [4,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%